Lower incidence of diabetes mellitus in patients with aneurysmal subarachnoid hemorrhage: a large case–control study with propensity score matching - Zhong, Weiying; Chen, Kai; Song, Ziyin; Xiao, Yizhou; Zhou, Donglin; Zhang, Mingxiang; Wang, Yunyan; Wang, Donghai; Su, Wandong (Frontiers in Neurology, 2023)
Background and purpose Diabetes mellitus (DM) is a well-established cardiovascular risk factor for atherosclerotic disease; however, its effect on the risk of rupture of intracranial aneurysms remains controversial. Herein, we aimed to perform a case–control study to investigate the relationship between DM and aneurysmal subarachnoid hemorrhage (aSAH). Methods We retrospectively reviewed the data of patients with ruptured or unruptured aneurysms who were treated between 2013 and 2023. Univariate and multivariate analyses were performed. Propensity score matching (PSM) analysis was conducted to evaluate the relationship between DM and risk of aSAH. Results A total of 4,787 patients with 5,768 intracranial aneurysms were included. Among them, 2,957 (61.8%) were females, 1765 (36.9%) had ruptured aneurysms, and 531 (11.1%) presented with DM. Female sex, current drinking, and hypercholesterolemia were associated with a higher risk of aSAH, whereas old age, former smoking, and DM were associated with a lower risk of aSAH in multivariate analysis (p < 0.05). The incidence of DM (13.4%, 406/3022) in the unruptured group was higher than that in the ruptured group (7.1%, 125/1765) (odds ratio, 0.55; 95% confidence interval, 0.444–0.680) (p < 0.001). After propensity score matching, 530 patients with DM were successfully matched, and DM was still associated with a lower risk of aSAH (odds ratio, 0.24; 95% confidence interval, 0.185–0.313) (p < 0.001). Conclusion Patients with aSAH have a lower incidence of DM, however, this case-cohort study could not establish a causal relationship. A prospective and large study with long-term follow-up is warranted to establish a causal relationship.